Participatory Governance in Secondary Schools: The Students’ View Point in Eastern Region of Kenya. - Mulwa, David M.; Kimosop, Maurice K.; Kasivu, Gedion M. (Journal of Education and Practice, 2015)
The purpose of the study was to determine the students’ view on participatory school governance in secondary schools of the Eastern region, Kenya. Participatory school governance implies the involvement of stakeholders in the decision making process in schools. The objectives of the study were to identify the key decision makers in selected management tasks in secondary schools as perceived by students in Eastern Region, Kenya and to establish the students’ opinion on their involvement in decision making in secondary schools of Eastern Region, Kenya. It was also meant to identify structures within the secondary school system which are used for students’ involvement in decision making process in secondary schools of Eastern Region, Kenya. The study adopted the descriptive survey research design. The target population was 28441 students of the secondary schools of Eastern Region of Kenya. A sample of 720 respondents was selected through multi-stage sampling procedures. Data was collected by the use of a questionnaire and was analyzed by the use of descriptive statistical tools. The findings were that the key decision makers in curriculum and design were the teachers, principals and students. In students’ management and welfare, it was the principals, teachers and Boards of Management while in schoolcommunity relations it was the principals. The students said that they should be involved in decision making and in their view, their involvement is very important. Though there is emphasis on the application of students’ governance through the students’ councils, students believe that since teachers’ interfere with the process of electing their leaders, then the structure of governance is the prefects system.
Keywords: Decision Making; Participatory school governance